Leisurely feelings: emotions and concepts of Otium in South Asia - Noor, Farha (Heidelberg Asian Studies Publishing (HASP), 2024)
This book traces a conceptual history of literature, leisure and emotions in modern South Asia. Reading colonial capitalism as entwined with the ‘myth of the lazy native’, it focuses on vernacular literary contestations in Urdu and Bengali. It foregrounds otium, leisure and idleness as entangled with emotions and temporalities. The book approaches literary spheres through the lenses of emotions, the self, and the community. Literary discourses of otium are analysed in stylistic innovations, negotiations of colonial modernity and postcolonial uncertainties. Highlighting key literary-conceptual expressions, discussions, and processes, the author explores nostalgia, melancholy, topophilia and haunting as emotions deeply attached to South Asian literary cultures while also resonating with concepts of otium across global modernity.
Keywords: Hochschulschrift; Begriffsgeschichte; Literaturgeschichtsschreibung; Gefühl; Muße; Südasien